Elsewhere (2017), volume 1 ebook - Faerber, Jay (Elsewhere (2017), 2018)
COPPERHEAD writer JAY FAERBER teams with rising star SUMEYYE KESGIN to unveil ELSEWHERE: the fantastic story of what really happened to Amelia Earhart. Mysteriously transported to a strange new world filled with flying beasts and alien civilizations, Amelia desperately struggles to return home. Along the way, she forges alliances and makes enemies as she goes from aviator to freedom fighter in a rebellion against a merciless warlord! Collects ELSEWHERE #1-4. Author: Jay Faerber. Illustrator: Sumeyye Kesgin . 2018 Jay Faerber & Sumeyye Kesgin.